Development of Homestay Door Locking System - Sanudin, Rahmat; Yunus, Nur Azalieda (Evolution in Electrical and Electronic Engineering, 2021)
Short term home rent is becoming more popular and trending lately due to its affordable rates and more value for money. Compared to staying in hotel or serviced apartments, it is more convenient and much cheaper to spend holiday in homestay for the majority of people. However, there are some issues of homestay especially related to safety issues. One of the most compelling issues is the authorised access of the homestay that is easily abused. Therefore, this project is intended to develop a reliable keyless door locking system to improve safety in homestay. The developed locking system offers flexible and convenient to guest, yet it is more secured than the conventional locking system. The prototype of locking system presented in this paper also has high potential to be installed in homestay.